Technology, design and the arts -- opportunities and challenges - Earnshaw, Rae; Liggett, Susan; Excell, Peter; Thalmann, Daniel (Springer Series on Cultural Computing, 2020)
This open access book details the relationship between the artist and their created works, using tools such as information technology, computer environments, and interactive devices, for a range of information sources and application domains.  This has produced new kinds of created works which can be viewed, explored, and interacted with, either.